Constructing respectability from disfavoured social positions: exploring young femininities and health as shaped by marginalisation and social context. A qualitative study in Northern Sweden. (23rd November 2018) - Wiklund, Maria; Ahlgren, Christina; Hammarström, Anne
ABSTRACT: Background : Gender, class and living conditions shape health and illness. However, few studies have investigated constructs of femininity in relation to health and living conditions among young women who are unemployed and marginalised at an early age. Objective : The aim of this research was to elucidate constructs of femininities in relation to structuring living conditions and expressions of health in Northern Swedish women. The time period of interest was the transition from unemployed teenagers to young adults in a social context of high unemployment and societal change across the critical 'school-to-work-transition' period of the life course. Methods : Qualitative content analysis was used to analyse data from repeated interviews with unemployed young women, aged 16–33 years, during the 1980s and 1990s. These longitudinal interviews were part of a cohort study in a 'remote' municipality in Northern Sweden that began in 1981. All girls who were not in education, employment, or training were selected for interview. An inductive analysis phase was followed by a theoretically informed phase. The contextual frame is the Nordic welfare-state model and the 'caring state' with its particular focus on basic and secondary education, and women's participation in the labour market. This focus paralleled high rates of youth unemployment in northern Sweden during the study period. Results : The results are presented as the theme of 'constructing respectability from disfavoured social positions'. Within this theme, and framed by dominant norms of patriarchal femininity, we explored the constructs of normative and altruistic, norm-breaking, and troubled femininity. Conclusions : Gender-sensitive interventions are needed to strengthen young women's further education and positions in the labour market and to preventing exposure to violence. More research on health experiences related to the multitude of constructs of femininities in various social contexts and across the life course is needed to help design and implement such interventions.